2017
DOI: 10.1108/jd-04-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy

Abstract: Purpose The purpose of this paper is to present a qualitative investigation into whether online textual postings, produced by undergraduate students as part of an undergraduate module, can demonstrate their information literacy (IL) capabilities as a discursive competence and socially enacted practice. It also asks whether these online postings embody power relations between students, tutors and librarians. Design/methodology/approach Foucault’s notion of discursive competence and the separate but complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Given these finding we argue that it is imperative that we attempt to enable all people to gain higher information discernment capabilities. Previous research (for example Walton and2013;Shenton and Pickard, 2014;Pickard, Shenton and Johnson, 2014;Walton and Cleland, 2017;Walton et al, 2018) has shown that this is achievable. The next section outlines a possible way of delivering effective information discernment teaching and learning.…”
Section: How Young People Make Judgements About Informationmentioning
confidence: 93%
“…Given these finding we argue that it is imperative that we attempt to enable all people to gain higher information discernment capabilities. Previous research (for example Walton and2013;Shenton and Pickard, 2014;Pickard, Shenton and Johnson, 2014;Walton and Cleland, 2017;Walton et al, 2018) has shown that this is achievable. The next section outlines a possible way of delivering effective information discernment teaching and learning.…”
Section: How Young People Make Judgements About Informationmentioning
confidence: 93%
“…Moreover, Zetina et al (2017) concluded that designing strategies for the adequate development of research competencies with the purpose of training sufficiently qualified young researchers is crucial. Walton and Cleland (2017) also presented qualitative research with the purpose of establishing whether students as part of a degree module can demonstrate through their online textual publications their IL skills as a discursive competence and social practice. Lopatovska and Sessions (2016) conducted a study examining reading strategies in relation to information-seeking stages, tasks and reading media in an academic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, the Bruce's relational model maps IL onto the different ways of experiencing it. The experiential nature of learning is tangible insofar as it involves continuous building, amending and eventually transforming previous knowledge structures (Walton & Cleland, 2017).…”
Section: Constructivist Approaches To Ilmentioning
confidence: 99%
“…Discourse analysis is heavily influenced by the work of Michel Foucault, for whom the central issue was to uncover the mechanisms in which social reality is produced. By "capturing the socially and culturally shaped ways of understanding information competencies and information practices" (Limberg et al, 2012, 110), discourse analysis recognizes language as central to social life, and a key to functioning in a society (Walton & Cleland, 2017).…”
Section: The Discourse Analytic Perspectivementioning
confidence: 99%